2012
DOI: 10.1523/jneurosci.2399-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Novel Animal Models of Acute and Chronic Cancer Pain: A Pivotal Role for PAR2

Abstract: Targeted therapy to prevent the progression from acute to chronic pain in cancer patients remains elusive. We developed three novel cancer models in mice that together recapitulate the anatomical, temporal and functional characteristics of acute and chronic head and neck cancer pain in humans. Using pharmacologic and genetic approaches in these novel cancer models, we identified the interaction between protease-activated receptor 2 (PAR2) and serine proteases to be of central importance. We show serine proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 28 publications
5
85
0
2
Order By: Relevance
“…Recent studies have revealed that in addition to the normal pain, PAR2 also plays a novel role in mediating acute and chronic cancer pain in the ectopic hind paw, head and neck cancer models [105,106] as well as bone cancer pain models [80,107,108]. Our study also demonstrated that subcutaneous administration of the PAR2 antagonist FSLLRY-NH2 almost completely abolished mechanical allodynia and thermal hyperalgesia in a rat model of bone cancer, without any effect on spontaneous pain behavior.…”
Section: G Protein-coupled Receptors 521 Protease-activated Receptorsupporting
confidence: 63%
“…Recent studies have revealed that in addition to the normal pain, PAR2 also plays a novel role in mediating acute and chronic cancer pain in the ectopic hind paw, head and neck cancer models [105,106] as well as bone cancer pain models [80,107,108]. Our study also demonstrated that subcutaneous administration of the PAR2 antagonist FSLLRY-NH2 almost completely abolished mechanical allodynia and thermal hyperalgesia in a rat model of bone cancer, without any effect on spontaneous pain behavior.…”
Section: G Protein-coupled Receptors 521 Protease-activated Receptorsupporting
confidence: 63%
“…Furthermore, supernatants from tumour cells, but not controls, caused marked and prolonged mechanical allodynia in wild type mice when administered into the hind paw. This effect was abolished by serine protease inhibitors and was absent in PAR 2 -deficient mice (Lam and Schmidt, 2010;Lam et al, 2012;Liu et al, 2013).…”
Section: Par 2 Signalling and Cancer Induced Painmentioning
confidence: 94%
“…In addition to a role in normal pain, recent studies have revealed that PAR2 plays a novel role in mediating acute and chronic cancer pain in ectopic hind paw, head, and neck cancer models (Lam et al 2012;Lam and Schmidt 2010), as well as bone cancer pain models (Bao et al 2013b;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%